Wednesday, 13 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.2397
|View full text |Cite
|
Sign up to set email alerts
|

OP0042 In acpa positive at-risk individuals, which mri and us findings best predict development of clinical synovitis?

Abstract: BackgroundACPA +individuals with non-specific MSK symptoms are at risk of inflammatory arthritis (IA) and may benefit from early intervention. Clinical, serological and US markers have previously been assessed to determine risk of progression.1 ObjectivesEvaluate the value of MR and US imaging in characterising and quantifying risk in a large ACPA +cohort.MethodsEligible ACPA +individuals without clinical synovitis had gadolinium enhanced 3.0 T MRI of the dominant hand and wrist. Images were scored by 2 radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…14,15 However, many consider PR as an at-risk phenomenon, which like other pre-RA conditions, like patients with inflammatory arthralgia, having periarthritis on magnetic resonance imaging, or ultrasound features for arthritis, was the most predictive of developing RA in the future. [16][17][18] The finding of RA-associated auto-antibodies in a large percentage of patients with PR could also be a reason for this hypothesis. 19,20 In addition, we have previously shown that PR treatment with a method like RA, that is with tight control strategy using combination of DMARDs, can prevent disease progression to chronic arthritis.…”
Section: Ta B L E 2 Outcomes Of Treatment With Mtx In 59 Patients Wit...mentioning
confidence: 98%
“…14,15 However, many consider PR as an at-risk phenomenon, which like other pre-RA conditions, like patients with inflammatory arthralgia, having periarthritis on magnetic resonance imaging, or ultrasound features for arthritis, was the most predictive of developing RA in the future. [16][17][18] The finding of RA-associated auto-antibodies in a large percentage of patients with PR could also be a reason for this hypothesis. 19,20 In addition, we have previously shown that PR treatment with a method like RA, that is with tight control strategy using combination of DMARDs, can prevent disease progression to chronic arthritis.…”
Section: Ta B L E 2 Outcomes Of Treatment With Mtx In 59 Patients Wit...mentioning
confidence: 98%
“… 35 50 95 Tenosynovitis was the only MRI abnormality associated with arthritis progression at patient level in a study of 98 ACPA+ individuals with MSK symptoms (HR 4.02 (1.91–8.44), p=0.002). 95 Similarly, tenosynovitis was the only MRI risk factor independently associated with arthritis development in a prospective study of 150 patients with CSA (HR 8.39 (3.38–20.81), p<0.001). There is also an increased prevalence of hand interosseous tendon inflammation in ACPA+ individuals with MSK symptoms.…”
Section: Resultsmentioning
confidence: 93%
“…41 GS synovitis in the wrists and MCP joints and PD signal in the MTP joints were all associated with development of RA in a UK cohort of patients with very early UA. 42 In a subsequent analysis of 107 patients with UA by In both ACPA-positive individuals with MSK symptoms and patients with CSA, subclinical inflammation on MRI has been associated with arthritis development [44][45][46] (table 4). In both populations, MRI tenosynovitis was the most prevalent MRI abnormality and also the most strongly associated with arthritis development.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…46 Similarly, at patient level, MRI tenosynovitis was the only MRI feature associated with arthritis development in a UK cohort of 98 ACPA-positive individuals with MSK symptoms (HR 4.02, 95% CI 1.9 to 8.4, p<0.01). 45 MRI findings in patients with UA are also associated with disease progression and specifically RA development. 47 48 In a small study of patients with recent-onset polyarthritis, MRI tenosynovitis of the finger flexor tendons and extensor carpi ulnaris, and synovitis of the radioulnar joint were associated with progression to RA.…”
Section: Clinical Featuresmentioning
confidence: 99%